2015
DOI: 10.1242/dev.117887
|View full text |Cite
|
Sign up to set email alerts
|

The non-canonical BMP and Wnt/β-catenin signaling pathways orchestrate early tooth development

Abstract: BMP and Wnt signaling pathways play a crucial role in organogenesis, including tooth development. Despite extensive studies, the exact functions, as well as if and how these two pathways act coordinately in regulating early tooth development, remain elusive. In this study, we dissected regulatory functions of BMP and Wnt pathways in early tooth development using a transgenic noggin (Nog) overexpression model (K14Cre;pNog). It exhibits early arrested tooth development, accompanied by reduced cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 73 publications
1
49
0
Order By: Relevance
“…Wnt signaling plays promotes early tooth development[2931], whereas excessive Wnt attenuates late tooth development [32, 33]. Inactivation of TGFβ type I receptor (ALK5) in neural crest cells leads to delayed tooth initiation and development [34].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling plays promotes early tooth development[2931], whereas excessive Wnt attenuates late tooth development [32, 33]. Inactivation of TGFβ type I receptor (ALK5) in neural crest cells leads to delayed tooth initiation and development [34].…”
Section: Discussionmentioning
confidence: 99%
“…In general, tooth morphogenesis is a process that is regulated by epithelial-mesenchymal interactions and during which the oral ectoderm thickens, buds, and invaginates to form a cap-like structure, and then a species-specific cusp34. Based on a common morphogenetic concept that a specific shape arises from local differences in cellular behavior regulated by signaling molecules, the cusp formation process involves spatiotemporal changes in cell number, size, shape, and position56.…”
mentioning
confidence: 99%
“…Currently three subfamilies of the Noggin family are known: Noggin1, Noggin2, and Noggin4 [1][2][3][4][5]. The data obtained in our laboratory demonstrated that secreted regulators Noggin1 and Noggin2 were involved in the binding to the proper ligands and inhi bition of three essential signal cascades, BMP, Nodal/Activin, and Wnt/betaCatenin [6,7]. The functions of the Noggin4 protein, which shares 35% homology with other members of the Noggin family and was only found in inferior vertebrates, are still unknown.…”
mentioning
confidence: 83%